2016
DOI: 10.3758/s13415-016-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Attention training improves aberrant neural dynamics during working memory processing in veterans with PTSD

Abstract: Posttraumatic stress disorder (PTSD) is associated with executive functioning deficits, including disruptions in working memory (WM). Recent studies suggest that attention training reduces PTSD symptomatology, but the underlying neural mechanisms are unknown. We used high-density magnetoencephalography (MEG) to evaluate whether attention training modulates brain regions serving WM processing in PTSD. Fourteen veterans with PTSD completed a WM task during a 306-sensor MEG recording before and after 8 sessions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Each participant completed 128 trials and the task lasted approximately 14 minutes. This same task was previously used in two normative studies and three other clinical studies by our group 21 28 36 37 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Each participant completed 128 trials and the task lasted approximately 14 minutes. This same task was previously used in two normative studies and three other clinical studies by our group 21 28 36 37 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, patients with PTSD exhibit abnormal oscillatory activity in prefrontal, supramarginal, and interior parietal regions that correlates with working memory deficit. These abnormalities are eliminated after successful attention training to improve working memory, suggesting that this biomarker can help monitor and evaluate treatment effectiveness [84].…”
Section: Human Studies: Identifying Activity-based Biomarkersmentioning
confidence: 99%
“…Recent developments in cognitive and neuroscientific interventions that aim to enhance working memory or improve attention control (McDermott et al, 2016), transcranial magnetic stimulation (TMS; Kozel et al, 2019), and new technologies such as virtual reality (Reger et al, 2016) have also shown promise as augmentation interventions.…”
Section: I) Enhancing Existing Treatmentsmentioning
confidence: 99%